User perception of academic library service quality and value: the case of the Ghana Institute of Journalism and Ashesi University College libraries - Nyantakyi-Baah, Lydia (Library and Information Studies Centre (LISC), 2017)
This study explored the users' perception of the service quality and value of the libraries of the Ghana Institute of Journalism (GIJ) and Ashesi University College (AUC). Concepts like value, impact, quality, academic library service quality formed the conceptual framework of the study. The study is a comparative case study that solicited information from the perspectives of students, faculty and library staff. Open and closeended questions were adopted to gather data from 185 and 147 third year students of GIJ and AUC respectively. All library staff and 15 faculty staff each from the two institutions were interviewed to augment the responses from the students. Statistical Package for Social Science was used to analyse the closed-ended questions and descriptive statistics such as frequencies and percentages were used to present the data analysis. Data from the interviews and open-ended questions were analysed qualitatively. Findings from the study showed that the libraries were used more frequently by students than by faculty staff. The perceptions of the quality of library staff services were found to be satisfactory in both libraries. The library environment and information resources were considered adequate by AUC library users, whereas they were considered as inadequate and poor at GIJ. In all, it was found that the quality of services and the value users derived from AUC exceeds that at GIJ. The most valued aspects of the libraries were the library collections, and the friendliness and willingness of library staff to assist users. It was also found that users derived a number of benefits from using the libraries, but the libraries had no specific guidelines for measuring their value. In the past, value had been determined by the use of the library resources and success stories of users. The study considered the nature of library value and made recommendations for improving library services.